2023
DOI: 10.1186/s12934-023-02021-5
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic stress constrains microbial L-cysteine production in Escherichia coli by accelerating transposition through mobile genetic elements

Abstract: Background L-cysteine is an essential chemical building block in the pharmaceutical-, cosmetic-, food and agricultural sector. Conventionally, L-cysteine production relies on the conversion of keratinous biomass mediated by hydrochloric acid. Today, fermentative production based on recombinant E. coli, where L-cysteine production is streamlined and facilitated by synthetic plasmid constructs, is an alternative process at industrial scale. However, metabolic stress and the resulting production e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…The genetic and phenotypic stability of microorganisms designed for the production of value-added products from carbonaceous biomass is a crucial issue in industrial biotechnology and one that is the subject of a growing body of work. Initial work on this subject focused on the stability of production systems in bacteria, where it was clearly shown that the use of plasmids carrying these production pathways is not advisable (see for instance [3]). Work on biomolecules-producing yeasts is less advanced, with a few works also revealing the problem of the stability of producing strains when the metabolic system is plasmid-based expressed [4, 5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The genetic and phenotypic stability of microorganisms designed for the production of value-added products from carbonaceous biomass is a crucial issue in industrial biotechnology and one that is the subject of a growing body of work. Initial work on this subject focused on the stability of production systems in bacteria, where it was clearly shown that the use of plasmids carrying these production pathways is not advisable (see for instance [3]). Work on biomolecules-producing yeasts is less advanced, with a few works also revealing the problem of the stability of producing strains when the metabolic system is plasmid-based expressed [4, 5].…”
Section: Discussionmentioning
confidence: 99%
“…In Escherichia coli , it was reported that the rise of frequencies of mobile element insertions in chromosomally-inserted transgenes is the main factor that interrupts production in mevalonic acid-producing cells [1]. Similarly, it has been shown that the metabolic stress induced by L-cysteine production in E. coli triggers insertion sequence (IS) transposition, resulting in structural genetic rearrangements in production plasmids that cause L-cysteine production capacities to drop by up to 65–85% within 60 generations [3]. Consequently, selective deletion of IS and their corresponding transposases could prove useful for stabilizing industrially production strains [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The often metabolically burdensome production drives populations to escape mechanisms. Within 60-70 generations, mutations can accumulate in the genome, giving cells a fitness advantage at the expense of production [4,5]. Thereby, mutations did not involve single-nucleotide polymorphisms but rather insertions of ISE into critical regions of synthetic plasmid constructs [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Within 60-70 generations, mutations can accumulate in the genome, giving cells a fitness advantage at the expense of production [4,5]. Thereby, mutations did not involve single-nucleotide polymorphisms but rather insertions of ISE into critical regions of synthetic plasmid constructs [4][5][6][7]. Insertions within genes can lead to mutations that result in loss-of-function.…”
Section: Introductionmentioning
confidence: 99%